Intervening Tango: Voices and Practices of Women and Dissidents in the Tango Scene of Buenos Aires, Argentina - Cecconi, Sofía (2025)
Introduction: This paper examines the intersections of tango, both as a musical production and a symbolic expression, with feminism and women and sexgeneric dissidents’ fight for their rights. Objective: From a Sociology of Culture approach, this study explores working practices and the production of new narratives within groups composed exclusively of women and dissidents. Methods: The methodological approach is qualitative-interpretative, consisting of in-depth interviews with leaders of musical groups, non-participant observations of their live performances, and the analysis of a corpus of tango lyrics. Results: The paper highlights various strategies aimed at intervening tango through new practices, forms of work and organization, and discourses, the new narratives produced. Through collective working methods, together with new lyrics and themes, these groups challenge, in diverse and creative ways, the patriarchal conventions that tango has canonized throughout its history. Conclusions: It was concluded that the new practices and discourses in tango, promoted by women and dissidents, challenge the hierarchical structures and create spaces of safety and belonging. These practices also reshape artistic production by incorporating themes that dismantle gender stereotypes and introduce new expressive forms across a variety of topics.